Randomized Trial to Compare the Immunogenicity and Safety of a CRM or TT Conjugated Quadrivalent Meningococcal Vaccine in Teenagers who Received a CRM or TT Conjugated Serogroup C Vaccine at Preschool Age. Issue 8 (August 2015) - Ishola, David A.; Andrews, Nick; Waight, Pauline; Yung, Chee-Fu; Southern, Jo; Bai, Xilian; Findlow, Helen; Matheson, Mary; England, Anna; Hallis, Bassam; Findlow, Jamie; Borrow, Ray; et al.
Abstract : Background: Protection after meningococcal C (MenC) conjugate (MCC) vaccination in early childhood is short-lived. Boosting with a quadrivalent vaccine in teenage years, a high-risk period for MenC disease, should protect against additional serogroups but might compromise MenC response. The carrier protein in the primary MCC vaccine determines the response to MCC booster in toddlers, but the relationship between primary vaccine and booster given later is unclear. This study compared responses to a CRM-conjugated or tetanus toxoid (TT)-conjugated MenACWY vaccine in teenagers primed with different MCC vaccines at preschool age. Methods: Ninety-three teenagers (16–19 years), who were previously randomized at age 3–6 years to receive single-dose MCC–CRM or MCC–TT, were randomized to receive either MenACWY–CRM or MenACWY–TT booster. Serum bactericidal antibodies (SBA, protective titer ≥8) were measured before, 1 month and 6 or 9 months after boosting. Results: Preboosting, MCC–TT-primed teenagers had significantly higher MenC SBA titers than those MCC–CRM-primed ( P = 0.02). Postboosting, both MenACWY vaccines induced protective SBA titers to all 4 serogroups in most participants (≥98% at 1 month and ≥90% by 9 months postboost). The highest MenC SBA titers were seen in those MCC–TT-primed and MenACWY–TT-boosted [geometric mean titer (GMT) 22, 000] followed by those boosted with MenACWY–CRM irrespective of priming (GMT 12, 000) and then those MCC–CRM-primed and MenACWY–TT-boosted (GMT 5500). The estimated postbooster MenC SBA decline beyond 1 month was 40% as time since booster doubles. Both vaccines were well tolerated with no attributable serious adverse events. Conclusion: Both MenACWY vaccines safely induced protective sustained antibody responses against all targeted serogroups in MCC-primed teenagers. Abstract : Supplemental Digital Content is available in the text.